Territorialities, health and environment:: connections, knowledge and quilombolas practices in Sergipe, Brazil (Sustainability in Debate, 2018)
The ecosystem approach to human health offers a theoretical and practical construction on the relations between health and environment based, among other factors, on the lifestyle of specific population groups. This study aimed to analyze how traditional principles and health care practices build territorialities that contribute to environmental conservation in quilombolas communities. Participant observation and interview with traditional healers were carried out in the communities of Mocambo and Sítio Alto, in the state of Sergipe. We identified the territoriality of resistance, the territoriality of care and the territoriality of hope as common features to both communities, in the articulation of knowledge and practices that connect health and environment. We concluded that the principles of the ecosystem approach to health were applied in the quilombolas communities and supported integrative and complex dynamics of relations between health and environment that contributed to the environmental and cultural conservation of these communities.